Technical Report. Incubation Program 2023 - Fuentes, A. (International Potato Center, 2023)
The incubation program is an intermediate training program in innovation and entrepreneurship, design for stu dents, researchers and entrepreneurs specialized in agrifood and triple impact business models. The program began on November 11 and finalized on December 20, 2023. This program is organized by the Business Incubator of the National Agrarian University La Molina (UNALM), Incubagraria in alliance with the International Potato Center (CIP) and executed in coordination with the Vice-Rectorate of Research of the UNALM. Within the results, 51 people were trained, 25 men and 26 women. The teaching modality was hybrid since some workshops were held online and others in person at the UNALM facilities. The main objective was to identify those innovative ventures based on science and technology with a prototype product and potential for positive social and/or environmental impact, and to help them fit their value proposal into the target market. This program is one of the activities developed within work package 5 of the CIP-CGIAR Resilient Cities Initiative. This work package aims to improve the research and innovation capabilities of UNALM researchers and students. For its part, the CIP-CGIAR Resilient Cities initiative is a global initiative implemented in 5 countries in Africa, Asia and Latin America and seeks to strengthen the capacities of urban food systems of the world's growing urban populations.